PENGARUH KEPEMIMPINAN, KECERDASAN EMOSIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN UD MITRA JAYA FARM - Subekti, Crystian; Zulistiani, Zulistiani; Bhirawa, Sigit Wisnu Setya (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The purpose this study is to analyze whether there is significant influence between the variables of leadership, emotional intelligence, and work motivation simultaneously or partially on the performance of UD Mitra Jaya Farm employees. The approach used in this study is quantitative approach and the type of causal relationship research, the sampling technique uses the Slovin formula, the sample size used is 50 employees, and the data analysis technique uses descriptive statistics, classical assumption test, multiple linear regression, coefficient of determination, and test hypothesis with SPSSv25 tool. The results showed that leadership and work motivation had a significant effect, emotional intelligence had no significant effect, and there was a significant influence on the simultaneous leadership, emotional intelligence, and work motivation variables on the performance of UD Mitra Jaya Farm employees.